Self-protection strategies and health behaviour in patients with inflammatory rheumatic diseases during the COVID-19 pandemic: results and predictors in more than 12 000 patients with inflammatory rheumatic diseases followed in the Danish DANBIO registry. Issue 1 (5th January 2021) - Glintborg, Bente; Jensen, Dorte Vendelbo; Engel, Sara; Terslev, Lene; Pfeiffer Jensen, Mogens; Hendricks, Oliver; Ostergaard, Mikkel; Horskjær Rasmussen, Simon; Adelsten, Thomas; Colic, Ada; Danebod, Kamilla; Kildemand, Malene; et al.
Abstract : Aims: In Danish patients with inflammatory rheumatic diseases to explore self-protection strategies and health behaviour including adherence to disease-modifying antirheumatic treatment (DMARD) during the initial phase of the COVID-19 pandemic and again after the reopening of the society started. Furthermore, to identify characteristics of patients with high levels of anxiety and self-isolation. Methods: Patients in routine care followed prospectively in the nationwide DANBIO registry were invited to answer an online questionnaire regarding disease activity and COVID-19 infection, behaviour in March and June 2020. Responses were linked to patient data in DANBIO. Characteristics potentially associated with anxiety, self-isolation and medication adherence (gender/age/diagnosis/education/work status/comorbidity/DMARD/smoking/EQ-5D/disease activity) were explored with multivariable logistic regression analyses. Results: We included 12 789 patients (8168 rheumatoid arthritis/2068 psoriatic arthritis/1758 axial spondyloarthritis/795 other) of whom 65% were women and 36% treated with biological DMARD. Self-reported COVID-19 prevalence was 0.3%. Patients reported that they were worried to get COVID-19 infection (March/June: 70%/45%) and self-isolated more than others of the same age (48%/38%). The fraction of patients who changed medication due to fear of COVID-19 were 4.1%/0.6%. Female gender, comorbidities, not working, lower education, biological treatment and poor European Quality of life, 5 dimensions were associated with both anxiety and self-isolation. Conclusion: In >12 000 patients with inflammatory arthritis, we found widespread anxiety and self-isolation, but high medication adherence, in the initial phase of the COVID-19 pandemic. This persisted during the gradual opening of society during the following months. Attention to patients' anxiety and self-isolation is important during this and potential future epidemics.